Polowanie na tygrysy w Polsce. Pero Tafur o Władysławie Jagiellończyku/Warneńczyku i o pewnym swoim pragnieniu (1438-1439) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The article analyzes the information contained in the description of the journey written by Pero Tafur. This information concerns the activities of the Polish king Władysław Jagiellończyk (Warneńczyk). So far, they have not been included in research dealing with the image of Poland in foreign messages. Pero Tafur, who came from Seville, made many trips to different countries in the years 1436-1439. He described his travels in Andanzas y viajes. He made pilgrimages to the Holy Land and Mount Sinai, he traveled around Egypt and the islands of the Mediterranean Sea. He also traveled around Europe. He carried out diplomatic and research missions for King John II of Castile. At the end of December 1438, he came to Wrocław to the court of Albrecht II, King of Germany, Bohemia and Hungary. The information contained in Andanzas y viajes concerning the war between Władysław Jagiellończyk and Albrecht II comes from the period of his stay in Wrocław. The traveler also met Władysław Jagiellończyk. During the meeting, Tafur expressed his desire to go to Krakow and participate in a great tiger hunt in Poland. The article shows how Tafur evaluates the young king of Poland. It was explained how the traveler’s information about tiger hunting in Poland can be understood. Tafur’s work is one of several travel works conveying their authors’ impressions of their stay in Poland.